Cross-Cultural encounters: the early reception of Charles Dickens in China, 1895-1915 - Lee, Klaudia Hiu Yen (2013)
This thesis examines the early reception of Charles Dickens in China from 1895 to 1915, with the aim of exploring the extent to which the values and politics that are purportedly embedded in Dickensian texts were interpreted and re-rendered for a totally different readership in a new place and time. I shall first introduce the publication and circulation history of Dickens's works in China during this first phase of cross-cultural transfer, and outline the theoretical underpinning of my research by arguing that the early Chinese translation of Dickens's works was a distinctive form both of translation and of adaptation, and one which was conditioned by specific cultural and historic contexts. I shall then focus on three main case studies-the Chinese translations and adaptations of Little Dorrit (1855-57), David Copperfield (1849-50) and A Tale a/Two Cities (1859)-to explore how different Dickensian features were re-enacted, or in cases subverted, during this crosscultural encounter. In Chapter One, I shall examine how Dickens's use of space and place in Little Dorrit is adapted and transformed by the Chinese translators, to the extent that the labyrinthine cityscape that characterised the author's portrayal of London is replaced by a gridlike structure that embodies traditional Chinese architectural principles. I shall also investigate how the social value and ideology as inscribed in built structures in Victorian England was transformed, and undermined during this adaptive process. In Chapter Two, I argue that traditional Chinese life writing, which was often used to exemplify wider history and culture instead of articulating the 'difference' of a bourgeois subject found in Western autobiographical traditions, has influenced the translation and adaptation of David Copperfield. I shall demonstrate the importance of examining these different traditions, and their impact on the way the text was adapted, against the two cultures' different conceptions of the self and of the individual at their respective historic moments. In Chapter Three, I shall first consider how in A Tale of Two Cities Dickens makes use of the French Revolution, and the antithesis between the individual and the collective, to comment on contemporary politics before proceeding to consider how the novel was adapted to serve specific political purposes when it was first published in China in an overtly political journal, The Justice, about a year and a half after the Chinese Revolution of 1911. I shall demonstrate the importance of reading the text in its original print contexts, and consider how the changes which the Chinese translator introduced to both the main text and the paratexts have transformed the politics of Dickens's original narrative. The influence of Chinese traditional historical writing on the adaptive text will also be explored. I shall conclude this thesis by situating it within the wider contexts of Victorian studies, arguing that my emphasis on cultural specificities and historical contingency challenges some of the methodologies and underlying assumptions pertaining to the 'global' turn of Dickens studies.